(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
Healthcare service delivery in Regional General Hospitals (RSUD) across North Sumatra Province faces mounting pressure due to rapid population growth and persistent nursing workforce deficits. This study aims to analyze the relationship between nurse workload and service quality across RSUDs in North Sumatra Province, and to identify strategic interventions capable of maintaining minimum service standards and patient safety. A descriptive-analytical quantitative approach was employed, utilizing secondary data from the BPS North Sumatra Province in Figures 2025–2026, National Quality Indicator (INM) reports from the Ministry of Health, and empirical findings from prior institutional studies conducted at Royal Prima Hospital Medan and Sari Mutiara Hospital Lubuk Pakam. The results reveal that the nurse ratio in North Sumatra stands at only 144.35 per 100,000 population, falling below the national standard of 158 per 100,000, while the Bed Occupancy Rate (BOR) at several major RSUDs reaches up to 87%. Correlation analysis confirms a significant negative relationship between excessive workload and nursing care quality (p < 0.05), with Hand Hygiene Compliance and Patient Fall Risk Prevention identified as the indicators most vulnerable to decline. Manual administrative burdens further reduce direct patient care time to below 80%, increasing the risk of Adverse Events (KTD) and nurse burnout. This study concludes that workforce redistribution using the Workload Indicators of Staffing Need (WISN) method and accelerated digitalization through Electronic Medical Records (EMR) and the SATUSEHAT platform are essential strategic responses to restore service quality and patient safety across North Sumatra’s regional hospital network.